Ductal carcinoma in situ: single center experience with 5-year follow-up - Gudavičienė, Daiva; Židonis, Žygimantas (Lietuvos chirurgija, 2016)
Introduction Ductal carcinoma in situ (DCIS) – heterogeneous group of diseases. Numbers of DCIS after introduction of breast cancer screening program, is constantly rising. Material and methods A retrospective analysis of 31 DCIS patient treated at National Cancer Institute in 2010 was performed. Patient ‘s age was 46– 75 years, average 60 y. 51.6% of cases were high grade DCIS, 9.6 % intermediate grade, 32.2 % low grade DCIS, and 3.2% Paget disease. 61.3% of cases were oestrogen positive (7–8 acc. Allred), and in 32.2 % of cases oestrogen receptors were negative. 61.3% of DCIS were progesterone positive, and in 35.5% progesterone receptors were negative. Usually DCIS was diagnosed performing mammography and radio-guided stereotactic biopsy, 67.7 %. In 70.1% radiologist evaluated mammography BI-RADS 4–6. In 45% radio-guided biopsy, and in 29.0% fine needle biopsy was performed. Results Patients were followed-up for 5 years. One patient died from ovarian cancer 60 month after DCIS surgery, and in 1 axillary metastases were found 61 months after DCIS surgery. Conclusions Age average of DCIS patients was 60 y., high grade DCIS, oestrogen and progesterone positive DCIS was dominant. After 5-year follow-up progression of disease, axillary metastases, was found in one patient (3,2 %).